2022
DOI: 10.1101/2022.12.30.522292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity and evolution of cerebellar folding in mammals

Abstract: The process of brain folding is thought to play an important role in the development and organisation of the cerebrum and the cerebellum. The study of cerebellar folding is challenging due to the small size and abundance of its folia. In consequence, little is known about its anatomical diversity and evolution. We constituted an open collection of histological data from 56 mammalian species and manually segmented the cerebrum and the cerebellum. We developed methods to measure the geometry of cerebellar folia … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Our study supports primate isometric cerebello-cerebral 50,51,89,118,126 evolution, tending towards hypo-allometry. A recent study reported similar and significant hypo-allometric cerebello-cerebral scaling across mammals 118 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our study supports primate isometric cerebello-cerebral 50,51,89,118,126 evolution, tending towards hypo-allometry. A recent study reported similar and significant hypo-allometric cerebello-cerebral scaling across mammals 118 .…”
Section: Discussionsupporting
confidence: 82%
“…Our study supports primate isometric cerebello-cerebral 50,51,89,118,126 evolution, tending towards hypo-allometry. A recent study reported similar and significant hypo-allometric cerebello-cerebral scaling across mammals 118 . When we reran PGLS in the Stephan sample, we observed the same cerebello-cerebral scaling coefficient as this study did (.92) 118 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations